A novel imatinib analogue inhibitor of chronic myeloid leukaemia: design, synthesis and characterization—explanation of its folded conformation - Rodolfo Moreno-Fuquen; Juan F. Avellaneda-Tamayo; Kevin Arango-Daraviña; Javier Ellena; Alan R. Kennedy (Royal Society Open Science)
Chronic myeloid leukaemia (CML) is primarily treated using imatinib mesylate, a tyrosine kinase inhibitor (TKI) targeting the BCR::ABL1 oncoprotein. However, the development of drug resistance and adverse side effects necessitate the exploration of alternative therapeutic agents. This study presents the synthesis and characterization of a novel imatinib analogue, 3-chloro-N-(2-methyl-5-((4-(pyridin-2-yl)pyrimidin-2-yl)amino)phenyl)benzamide (PAPP1). The compound’s structure was elucidated using X-ray crystallography and spectroscopic techniques, including NMR, infrared and UV–visible. Crystallographic analysis reveals that PAPP1 consists of a phenyl–amino–pyridine–pyrimidine (PAPP) scaffold with substituted aromatic rings forming a nearly coplanar geometry. Additionally, supramolecular interactions in the crystal are mediated by hydrogen bonds and dispersion forces, forming dimers and layered structures. Molecular docking studies demonstrate strong binding affinity to the ABL1 enzyme, with PAPP1 showing comparable binding energy to imatinib, indicating its potential as a lead compound for further development. Computational studies, including molecular electrostatic potential and vibrational analysis, provide further support for the structural stability and bioactivity of PAPP1. These findings suggest that PAPP could be a promising scaffold for future CML drug design, offering a potential alternative to existing TKIs, and PAPP1 is a promising lead susceptible to optimization.